Wave Propagation Concepts for Near-Future Telecommunication Systems 2017
DOI: 10.5772/66663
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Electromagnetic Waves with Zero Index Materials

Abstract: Zero-index material is a typical metamaterial with an effective zero refractive index, possessing a variety of exotic electromagnetic properties and particular functionalities. We have considered two kinds of zero-index materials with the first one a nearly matched zero index made of magnetic metamaterial and the second one a radially anisotropic zero index. The magnetic metamaterial-based systems are shown to be significant in wavefront engineering and flexibly tunable by an external magnetic field and a temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…This remarkable quality implies the total reflection of EM waves incident on the wormhole [21,22]. On the other hand, recent research on near-zero permittivity metamaterials has revealed a number of exotic EM properties like, for instance, 'squeeze the EM wave and make it tunnel through a deep subwavelength channel with arbitrary shape' [23]. This offers a perspective of building metamaterial-based analog models for further study of the charged wormhole spacetime.…”
Section: Charged Wormhole Spacetimementioning
confidence: 99%
“…This remarkable quality implies the total reflection of EM waves incident on the wormhole [21,22]. On the other hand, recent research on near-zero permittivity metamaterials has revealed a number of exotic EM properties like, for instance, 'squeeze the EM wave and make it tunnel through a deep subwavelength channel with arbitrary shape' [23]. This offers a perspective of building metamaterial-based analog models for further study of the charged wormhole spacetime.…”
Section: Charged Wormhole Spacetimementioning
confidence: 99%